Niveles séricos de urea y creatinina en los trabajadores agricultores de los fundos “Macaby bajo” y “La Arenita” del distrito de Paijan, provincia de Ascope – departamento de La Libertad - mayo - 2008 - Torres Valdez, María del Carmen (2008)
Levels were determined creatinine and urea plasma Workers at the Farmers' Fund "Macaby Under" and "Arenita," District Paijan - Ascope Province, Department of La Libertad, conducting talks about the issue, distributed informational brochures. 106 blood samples were processed according to specific methods for the determination of urea and creatinine; results were submitted to the Student t-test, the test Nonparametric independence of criteria using the distribution Chi-Square and the correlation coefficient Pearson. Demonstrating the existence of the relationship between sex and the concentration of creatinine and the increase in systolic with it. The normal values for which the urea were 24.53% and 73.59% represents high levels and creatinine levels with a high 65.1%, with levels decreased 16.98% and 17.92% normal. According to the determination workers and especially males are more prone to contracting a kidney disease.